Ophthalmology Current Clinical and Research Updates - Davey, Pinakin (IntechOpen, 2014)
This book brings together both a review and updates in clinical and research areas. The chapters will be of interest to a wide audience. On one hand, the review and update of clinical practices will interest students and residents, on the other, cutting edge research chapters will be of interest to the researchers in the field. The book is divided into four parts: 1) Review and Updates in Diagnostic Testing, 2) Updates in Anterior Segment Diseases, 3) Updates in Posterior Segment Diseases, and 4) Updates in Research in Ophthalmology, Optometry and Vision Science. The chapters are written by experts and individuals with special interests in topics with a focus on clinical application and translational benefit to eye care.